Role of acoustic cavitation in the delivery and monitoring of cancer treatment by high-intensity focused ultrasound (HIFU). - Coussios, C; Farny, C; Haar, G; Roy, R (2007)
Acoustic cavitation has been shown to play a key role in a wide array of novel therapeutic ultrasound applications. This paper presents a brief discussion of the physics of thermally relevant acoustic cavitation in the context of high-intensity focussed ultrasound (HIFU). Models for how different types of cavitation activity can serve to accelerate tissue heating are presented, and results suggest that the bulk of the enhanced heating effect can be attributed to the absorption of broadband acoustic emissions generated by inertial cavitation. Such emissions can be readily monitored using a passive cavitation detection (PCD) scheme and could provide a means for real-time treatment monitoring. It is also shown that the appearance of hyperechoic regions (or bright-ups) on B-mode ultrasound images constitutes neither a necessary nor a sufficient condition for inertial cavitation activity to have occurred during HIFU exposure. Once instigated at relatively large HIFU excitation amplitudes, bubble activity tends to grow unstable and to migrate toward the source transducer, causing potentially undesirable pre-focal damage. Potential means of controlling inertial cavitation activity using pulsed excitation so as to confine it to the focal region are presented, with the intention of harnessing cavitation-enhanced heating for optimal HIFU treatment delivery. The role of temperature elevation in mitigating bubble-enhanced heating effects is also discussed, along with other bubble-field effects such as multiple scattering and shielding.